Ghrelin receptor modulates T helper cells during intestinal inflammation. Issue 11 (30th July 2015) - Di Giovangiulio, M.; Stakenborg, N.; Bosmans, G.; Meroni, E.; Farro, G.; Gomez‐Pinilla, P. J.; Depoortere, I.; Boeckxstaens, G. E.; Matteoli, G.
Abstract Background The orexigenic peptide ghrelin has anti‐inflammatory properties in colitis, however, the mechanism of action and the immune cells targeted remain still to be elucidated. Here, we assessed the possible effect of ghrelin on T helper (Th) cells in a T cell transfer model of chronic colitis. Methods Disease was induced in the recombination activating gene 1 knockout mice (Rag1−/−) by adoptive transfer of naïve Th cells from ghrelin receptor knockout mice (GRLN‐R−/−) or littermate wild‐type (WT) mice. The course and severity of colitis was assessed by monitoring body weight, diarrhea score, histological analysis, gene expression, and flow cytometry analysis. The possible effects of ghrelin on Th cell proliferation, polarization, and apoptosis was examined in vitro. Key Results Our data showed that Rag1−/− mice injected with GRLN‐R−/− Th cells displayed increased severity of colitis compared to mice injected with WT Th cells. In addition, Rag1−/− mice injected with GRLN‐R−/− Th cells had significantly higher intestinal inflammation and increased accumulation of Th1 and Th17 cells in the colon. In vitro, ghrelin directly affected proliferation of Th cells and induced apoptosis whereas it did not influence Th cell polarization. Conclusion & Inferences Our observations suggest that ghrelin modulates Th effector cells in the gut controlling proliferation and inducing apoptosis. Our findings further support the use of ghrelin as a novel therapeutic option to treat intestinal inflammatory diseases.